Unveiling the Sway of Marketing Mix on Student Decisions: A Study on Higher Learning Institutions: Mengungkap Pengaruh Bauran Pemasaran terhadap Keputusan Mahasiswa: Sebuah Studi pada Institusi Pendidikan Tinggi - Febriansah, Rizky Eka; Yani, Muhammad; Prasojo, Bayu Hari (Indonesian Journal of Law and Economics Review, 2023)
This research delves into the pivotal process of student decision-making within higher learning institutions, focusing on the dynamic interplay of marketing mix services encompassing product, price, promotion, and place. Through an analysis of alumni and current student cohorts at a prominent university, this study empirically demonstrates the profound influence exerted by product quality, strategic promotion, and favorable institutional positioning on students’ selection choices. Notably, while price emerges as a comparatively weaker determinant, the collective impact of product, place, and promotion proves instrumental in shaping prospective students’ decisions. These findings illuminate the complex landscape of student preferences, offering valuable insights for crafting targeted marketing strategies that effectively guide students’ educational trajectories. Highlight: Influence of Marketing Mix Dynamics: This study examines the interaction of product, price, promotion, and place in shaping student decisions within higher learning institutions, revealing their collective impact on choice. Empirical Insights: Analysis of alumni and current students from a renowned university highlights the significant sway of product quality, strategic promotion, and favorable institutional positioning on student selection choices. Role of Price in Decision-making: While price emerges as a less potent factor, the study underscores the pivotal role played by the interplay between product, place, and promotion in molding the educational preferences of prospective students. Keyword: Student Decision-Making, Higher Learning Institutions, Marketing Mix Services, Product Quality, Strategic Promotion